Analisis Potensi Sebaran Paham Radikalisme dalam Proses Perkuliahan Daring di UIN Sunan Ampel Surabaya - Murthi, Narindra Krisna (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2022)
The Covid pandemic has proven not only to have an impact on the health and economic sectors, but also education. On the other hand, the national security sector is also threatened, with the opportunity for terrorist groups to take advantage of the chaos situation. This study focuses on the potential threat of the spread of radicalism, which targets students, especially UINSA students during the online lecture process. The results of this study indicate that there is an opportunity for a shift in the methods used by terrorist groups to influence students, namely with the rise of Cyberterrorism during the Pandemic. This study explains this phenomenon using qualitative research methods and describes the results of questionnaires filled out by students of UIN Sunan Ampel Surabaya, as the basis for the potential for the spread of radicalism through the internet and social media, which are currently the main learning platforms.